“Diferentes niveles de nitrógeno, fósforo y potasio en la producción de tabaco negro variedad HRE-33 en el sector aeropuerto - Tarapoto” - Grandez Paredes, Roberto (2007)
The following work is about levels of Nitrogen, 1 Phosphorate and Potassium in the black tobacco production variety HRE-33 in the sector airport of Tarapoto".; 1 am made the objective, to establish the adapted dose of fertilization that allows to stay a better yield of the tobacco black variety HRE-33, in the sector airport - Tarapoto and to determine the economic analysis of the treatments by means of the relationship benefits cost;. located in the Populated Center smaller than Santa Rosa of Cumbaza on "I Found Santa Rosillo", to 5 Km. of the city of Tarapoto.; with an annual maximum Tº of 32 ºC, precipitation averages yearly of 1 200 mm anda relative humidity of 70- 80%. The ~s'ed design was at random of Complete Blocks (DBCA), with 5 treatments and 4 repetitions. Thei treatments were T1 (143-128-209), T2 (85-113-80), T3 (100- 90-110) T4 (72-40-90), T5 (0-0-0), evaluanting itself. height of plants, number of leaves, weight of green, long and wide of the leaf, dry green relation of the leaf, yield of the dry leaf, The results demonstrated that the biggest yields of dry leaf for hectare were obtained in the treatment 1(143-128-209) that 1reach2607, 25 Kg. that it gave to the net utility of SI. 9 282, 37 new suns under conditions of Tarapoto .